Superior inhibitory control and resistance to mental fatigue in professional road cyclists - Martin, K.; Staiano, W.; Menaspa, P.; Hennessey, T.; Marcora, S.; Keegan, R.; Thompson, K. G.; Martin, D.; Halson, S.; Rattray, B. (PLOS ONE, 2016)
Given the important role of the brain in regulating endurance performance, this comparative study sought to determine whether professional road cyclists have superior inhibitory control and resistance to mental fatigue compared to recreational road cyclists. Methods: After preliminary testing and familiarization, eleven professional and nine recreational road cyclists visited the lab on two occasions to complete a modified incongruent colour-word Stroop task (a cognitive task requiring inhibitory control) for 30 min (mental exertion condition), or an easy cognitive task for 10 min (control condition) in a randomized, counterbalanced cross-over order. After each cognitive task, participants completed a 20-min time trial on a cycle ergometer. During the time trial, heart rate, blood lactate concentration, and rating of perceived exertion (RPE) were recorded. Results: The professional cyclists completed more correct responses during the Stroop task than the recreational cyclists (705±68 vs 576±74, p = 0.001). During the time trial, the recreational cyclists produced a lower mean power output in the mental exertion condition compared to the control condition (216±33 vs 226±25 W, p = 0.014). There was no difference between conditions for the professional cyclists (323±42 vs 326±35 W, p = 0.502). Heart rate, blood lactate concentration, and RPE were not significantly different between the mental exertion and control conditions in both groups. Conclusion: The professional cyclists exhibited superior performance during the Stroop task which is indicative of stronger inhibitory control than the recreational cyclists. The professional cyclists also displayed a greater resistance to the negative effects of mental fatigue as demonstrated by no significant differences in perception of effort and time trial performance between the mental exertion and control conditions. These findings suggest that inhibitory control and resistance to mental fatigue may contribute to successful road cycling performance. These psychobiological characteristics may be either genetic and/or developed through the training and lifestyle of professional road cyclists.